Essentials of statistical analysis "In Focus" : alternate guides for R, SAS, and Stata for essential statistics for the behavioral sciences /: alternate guides for R, SAS, and Stata for essential statistics for the behavioral sciences. (2018) - Privitera, Gregory J; Sotak, Kristin L; Lei, Yu
No abstract available